Are Auditors' Judgments Sufficiently Regressive? - Joyce, Edward J.; Biddle, Gary C. (Journal of Accounting Research, 1981)
The primary purpose of this paper is to test for the use of the representativeness heuristic by auditors in situations in which its use will lead to judgments that systematically depart from the Bayesian optimal responses. No explicit representation of payoffs was made, nor were subjects typically asked to choose a course of action. Thus it cannot be concluded that use of the representativeness heuristic in the experimental situations tested is not cost effective. To the extent, however, that one is willing to assume that action choices are sensitive to judgments of outcome probabilities, and these action choices have differential expected payoffs, a finding of extensive heuristic use by auditors would suggest further research to assess the economic consequences of such use.